Tenth of December : stories - Saunders, George, 1958- (New York : Random House, 2013)
A collection of stories includes "Home," a wryly whimsical account of a soldier's return from war; "Victory Lap," a tale about an inventive abduction attempt; and the title story, in which a suicidal cancer patient saves the life of a young misfit.
Victory lap -- Sticks -- Puppy -- Escape from Spiderhead - - Exhortation -- Al Roosten -- The semplica girl diaries - - Home -- My chivalric fiasco -- Tenth of December.
Keywords: Short stories, American. 95 holds on first copy returned of 28 copies LOCATION CALL NO. STATUS APL New Fiction FIC Saunders, G. DUE 02-27-13 Bailey New Fiction SAUNDERS DUE 03-06-13 Baxter ML Adult Fiction F Sau DUE 03-12-13 Camden PL New Fiction F Sau DUE 02-14-13 Camden PL New Fiction F Sau c.2 DUE 03-06-13 CML Adult Fiction NEW FIC Saunders G DUE 03-20-13 Falmouth ML Fiction F Saunders DUE 03-08-13 Gardiner PL Adult New Fic F S257 DUE 03-19-13 Jesup ML Fiction SAUNDERS DUE 03-08-13 LewPL New Books F Saunde,G DUE 03-12-13